2013
DOI: 10.1182/blood-2012-09-453894
|View full text |Cite
|
Sign up to set email alerts
|

Genetic elimination of the binding motif on fibrinogen for the S. aureus virulence factor ClfA improves host survival in septicemia

Abstract: Fibrinogen can support host antimicrobial containment/clearance mechanisms, yet selected pathogens appear to benefit from host procoagulants to drive bacterial virulence. Here, we explored the hypothesis that host fibrin(ogen), on balance, supports Staphylococcus aureus infection in the context of septicemia. Survival studies following intravenous infection in control and fibrinogen-deficient mice established the overall utility of host fibrin(ogen) to S. aureus virulence. Complementary studies in mice express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 50 publications
4
81
0
Order By: Relevance
“…For example, the elimination of host fibrin(ogen) significantly reduced the virulence of S aureus in the context of an intravenous infection challenge. 14 In contrast, in studies of S aureus peritonitis, fibrin(ogen) deficiency favored the virulence of the pathogen by impeding the rapid clearance of bacteria in the peritoneal cavity. 15,16 Similar studies using mice with a genetically imposed reduction in circulating prothrombin or pharmacologic inhibition of thrombin activity also resulted in significantly compromised S aureus clearance from the peritoneal cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the elimination of host fibrin(ogen) significantly reduced the virulence of S aureus in the context of an intravenous infection challenge. 14 In contrast, in studies of S aureus peritonitis, fibrin(ogen) deficiency favored the virulence of the pathogen by impeding the rapid clearance of bacteria in the peritoneal cavity. 15,16 Similar studies using mice with a genetically imposed reduction in circulating prothrombin or pharmacologic inhibition of thrombin activity also resulted in significantly compromised S aureus clearance from the peritoneal cavity.…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53][54][55] Interestingly, in the setting of intravenous S aureus infection (bacteremia), fibrinogen supports pathogen virulence and investigator-imposed fibrinogen deficiency improves host survival, 14 whereas in the setting of S aureus peritonitis, fibrinogen diminishes pathogen virulence and investigator-imposed fibrinogen deficiency impedes bacterial clearance and reduces host survival. 15 An impediment in the clearance of S aureus in the peritoneal cavity was also documented for mice carrying a mutant form of fibrinogen lacking the a M b 2 binding motif but maintaining full clotting function.…”
Section: Arg16cysmentioning
confidence: 99%
“…Agglutination with fibrin fibrils protects staphylococci from phagocytes and promotes the formation of infectious thrombi that contribute to the lethal outcome of staphylococcal sepsis in mice (4,10). Staphylococcal agglutination is also essential for the pathogenesis of infectious endocarditis and the formation of purulent abscess lesions, which promote bacterial persistence and dissemination in host tissues (11)(12)(13).…”
mentioning
confidence: 99%
“…Importantly, in 2009, we were able to study the association between CLL and MBL among 77 469 healthy adults who were enrolled in the nationwide, population-based Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial. 4 In that study, we identified 45 patients in whom CLL was subsequently diagnosed (up to 6.4 years later) through the collection of a peripheral blood sample. By using 6-color flow cytometry (with antibodies CD45, CD19, CD5, CD10, k, and l) and immunoglobulin heavy-chain gene rearrangement by reverse-transcription polymerase chain reaction assay, we determined the association between MBL and subsequent CLL and characterized the immunoglobulin gene repertoire of the prediagnostic B-cell clones.…”
Section: Conflict-of-interest Disclosurementioning
confidence: 99%
“…Some examples are antimicrobial host protection, inflammatory reactions, angiogenesis, wound healing, interactions with extracellular matrix components, and fibrin(ogen)olysis. [3][4][5][6] Surprisingly, although we know that fibrinogen is sufficient for platelet adhesion and aggregation in vitro, we do not even know the relative roles of fibrinogen vs fibrin in platelet aggregation in vivo. It is intuitively clear that insoluble fibrin polymer is made to perform special tasks that are distinct from the roles of the soluble monomeric plasma protein fibrinogen; for example, the mechanical properties of hemostatic clots and thrombi are determined by fibrin, not fibrinogen.…”
mentioning
confidence: 99%